2022
DOI: 10.1039/d2ja00102k
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the analytical 183W effect and its implications for tungsten isotope analyses

Abstract: Mass-independent tungsten isotope variations provide critical insights into the timing and nature of processes that occurred in the early Solar System and during planetary differentiation. However, W isotope analyses are...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 89 publications
(245 reference statements)
1
19
0
Order By: Relevance
“…23,26,27 Similar effects have been observed for other elements ( e.g. , Ti, 71 Ni, 72 Mo, 73 W 74 ), and have been interpreted as possibly stemming from the elemental purification/enrichment production process ( e.g. , Kroll process) and/or non-exponential mass-dependent fractionation during the genesis of the ores used to make these standards.…”
Section: Discussionmentioning
confidence: 59%
“…23,26,27 Similar effects have been observed for other elements ( e.g. , Ti, 71 Ni, 72 Mo, 73 W 74 ), and have been interpreted as possibly stemming from the elemental purification/enrichment production process ( e.g. , Kroll process) and/or non-exponential mass-dependent fractionation during the genesis of the ores used to make these standards.…”
Section: Discussionmentioning
confidence: 59%
“…Prior studies proposed that analytical 183 W deficits are the result of a nuclear field shift effect (Cook & Schönbächler, 2016), but Budde et al. (2022) showed that this is unlikely to be the cause. Instead, Budde et al.…”
Section: Discussionmentioning
confidence: 99%
“…As the parameters of such regressions are specific to a certain analytical protocol (and possibly even operator), here we use a regression of terrestrial GRMs (JG-1, JR-1, JA-2, and JB-2) and mid-ocean ridge basalt (MORB sample PS66-261) doped with variable amounts of the Alfa Aesar W solution standard based on our own data. For more details about analytical 183 W deficits and their causes, we refer the reader to Budde et al (2022).…”
Section: Correction Of Analytically Induced 183 W Deficits (Ie "The 1...mentioning
confidence: 99%
“…The W isotopic mass fractionation correction was performed by normalisation to 186 W/ 184 W = 0.92767 according to the exponential law, which is noted as N6/4 (Rosman and Taylor 1997, Kruijer and Kleine 2018, Budde et al . 2022). Each sample was preceded and followed by the measurements of the Alfa Aesar W standard and the mean 182 W/ 184 W ratio bracketed was used to calculate μ 182 W N6/4 :normalμ182normalWN6/4=)()(182normalW/184normalWN6/4sample/)()(182normalW/184normalWN6/4standard1×106…”
Section: Methodsmentioning
confidence: 99%